Women’s Town in the Sāmnameh and Its Footprints in Persian Literature - Majid Pooyan; Mohammadreza Najarian; Elham Hasanshahi (Matn/Pizhūhī-i Adabī, 2020)
A number of narratives and fictional poems in Persian literature describe women who are warriors and self-reliant. These women lived together, separated from men, and controlled their lives. Most of the Eskandarnamehs depict these women. The Sāmnameh makes a brief reference to it. Women's Town (Shahr-e zanān), which is a recurring theme in fiction, is discussed in this article along with the Sāmnameh. The purpose of this study is to examine the appearance and manifestation of this city in the works examined and to analyze its features, foundations, and themes. These cases are compared with the themes and features described in the Sāmnameh so as to clarify the similarities and differences between these narrations, as well as their origins. Accordingly, the following conclusion can be drawn: In the Women's Town of other texts (Eskandarnamehs), there is no lustful desire on the part of the hero. On the other hand, in the Women's Town of Sāmnameh, the lustful desires of the women and fairies are exaggerated. There is more to this story than just Eskandarnamehs and Amazons from Greek and Roman mythology. Therefore, the story's origins may be found in Iranian mythology or in a combination of Iranian and Greek mythology, both of which are controversial.